2018
DOI: 10.1016/j.urology.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable Hydrogel Spacer Use in Prostate Radiotherapy: A Comprehensive Review of Phase 3 Clinical Trial Published Data

Abstract: Prostate-rectum hydrogel spacer application is a relatively safe technical procedure that is well tolerated and has a high technical success rate. Spacer application significantly reduces rectal radiation dose and results in long-term reductions in rectal toxicity, as well as improvements in bowel, urinary, and sexual QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
83
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 29 publications
2
83
0
4
Order By: Relevance
“…Prostate-rectum separation achieved leads to improving dosimetric rectal profiles even with a minimal prostateerectum separation rectal doses can significantly reduce because of the rapid dose fall off with BT. These results are consistent with other EBRT-specific reports (10,13). Of the 615 patients, there were 26 patients that the placement of hydrogel spacer was not successful because of technically failures during implantation such as insufficient hydrodissection, and injection of hydrogel into the rectal lumen (25,28).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Prostate-rectum separation achieved leads to improving dosimetric rectal profiles even with a minimal prostateerectum separation rectal doses can significantly reduce because of the rapid dose fall off with BT. These results are consistent with other EBRT-specific reports (10,13). Of the 615 patients, there were 26 patients that the placement of hydrogel spacer was not successful because of technically failures during implantation such as insufficient hydrodissection, and injection of hydrogel into the rectal lumen (25,28).…”
Section: Discussionsupporting
confidence: 89%
“…As a consequence, the application of rectal displacement devices resulted in a decrease of acute and late rectal toxicity from EBRT (9e16). Randomized studies demonstrated the clinical benefit of PEG hydrogel spacer in terms of acute and late rectal toxicities during prostate EBRT (10). Recently, several studies have been investigated the role of PEG hydrogel spacers during prostate BT in the different setting.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Several studies report the feasibility of hydrogel rectal spacers in patients receiving primary radiation for prostate cancer. [13][14][15][16][17][18] A recent UC patient case report demonstrated the successful treatment with Ir-192 brachytherapy for primary PC, after SpaceOAR gel injection. The patient reported no bowel issues following HDR brachytherapy after one day, one week and five months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal sparing devices such as hydrogel spacers offer the prospect of increased space between the prostate and rectum, causing reduced rectal dose and potentially reduced injury. [3][4][5][6][7] However, there are drawbacks to offering an RSD to all patients. With an invasive procedure such as transperineal hydrogel insertion there are inherent adverse risks to the patient such as rectal infiltration, rectal ulceration, and infection, although reportedly low so far.…”
Section: Introductionmentioning
confidence: 99%